Controlled attenuation parameter is correlated with actual hepatic fat content in patients with non‐alcoholic fatty liver disease with none‐to‐mild obesity and liver fibrosis. Issue 10 (15th March 2016) - Fujimori, Naoyuki; Tanaka, Naoki; Shibata, Soichiro; Sano, Kenji; Yamazaki, Tomoo; Sekiguchi, Tomohiro; Kitabatake, Hiroyuki; Ichikawa, Yuki; Kimura, Takefumi; Komatsu, Michiharu; Umemura, Takeji; Matsumoto, Akihiro; et al.
Abstract : Aim: Non‐invasive steatosis‐quantifying methods are required for non‐alcoholic fatty liver disease (NAFLD) patients in order to monitor disease severity and assess therapeutic efficacy. Controlled attenuation parameter (CAP) evaluated with vibration‐controlled transient elastography can predict the presence of steatosis, but its application to absolute hepatic fat quantitation remains unclear. The aim of this st\udy was to examine whether CAP is correlated with real hepatic fat content in NAFLD patients. Methods: Eighty‐two NAFLD patients who had undergone percutaneous liver biopsy were enrolled. CAP was measured using FibroScan ® just before liver biopsy. The percentage of fat droplet area to hepatocyte area in biopsied specimen was determined morphometrically using computerized optical image analyzing system. The correlation between CAP and liver histology was examined. Results: CAP showed an excellent correlation with actual liver fat percentage in the NAFLD patients with body mass index (BMI) of less than 28 kg/m 2 ( r  = 0.579, P  < 0.0001), especially less than 25 kg/m 2 ( r  = 0.708, P  < 0.01), but the meaningful correlation disappeared in the patients with BMI of 28 kg/m 2 or more. In the patients with BMI of less than 28 kg/m 2, CAP quantitativeness was affected by the presence of stage 2–4 fibrosis, but not the presence of hepatocyte ballooning and severity of lobular inflammation. Conclusion: CAP may be a promising tool for quantifying hepatic fat content in NAFLD patients with none‐to‐mild obesity and liver fibrosis. Further improvement of CAP performance is needed for the NAFLD patients with BMI of more than 28 kg/m 2 or significant hepatic fibrosis.